Riverbank erosion as an impediment to rural development in Bangladesh: the applicability of system theory - Hamide, Md. Shamim; Karim, A.H.M Zehadul (International Sciences Community Association, 2017)
This paper contributes to the broad-ranging topic of natural disaster management from a sociological perspective. In particular, it draws attention to the relevance of System Theory and advocates its suitability for designing frameworks to understand natural disaster phenomenon, which grab the head insidious, and equally vicious disasters like riverbank erosion in Bangladesh. This holds especially true for impoverished regions of the world like South Asia, which are still predominantly agrarian and rural.